Designing Meaningful Lessons: Barriers and Solutions in Instructional Planning Among Indonesian Prospective EFL Teachers - Kusriandi, Wendi; Herawan, Endang; Aminah, Neneng; Bin Mamat, Noordin (Universitas Hamzanwadi, 2025)
Instructional planning is widely recognised as essential for effective teaching, yet prospective teachers often lack the knowledge, experience, and resources to design context-responsive lessons. Research on lesson planning has predominantly focused on in-service teachers, leaving limited insight into the multidimensional barriers teacher candidates face in Indonesian EFL contexts, particularly within private universities. This qualitative case study addresses this gap by examining two guiding questions: (1) What factors hinder prospective teachers in designing instructional plans? Moreover, (2) What solutions can effectively address these barriers? Three purposively selected eighth-semester students from the English Language Education Study Program at a private university in Indonesia were studied based on scaffolding principles. Data were triangulated through open-ended questionnaires, semi-structured interviews, and document analysis, and then analysed thematically with member checking to ensure trustworthiness. Findings highlight three interconnected challenges: limited mastery of pedagogical vocabulary and authentic material development, misalignment between methods and materials, and a persistent gap between theoretical coursework and practical classroom dynamics. Proposed solutions include intensive tiered mentoring by lecturers and supervising teachers, integration of authentic locally relevant materials, and real-case-based lesson design workshops. These findings contribute to teacher education research by offering evidence-based recommendations for curriculum reform and practicum design that strengthen prospective teachers’ competence in creating meaningful and contextually grounded lesson plans.